2002
DOI: 10.3141/1811-20
|View full text |Cite
|
Sign up to set email alerts
|

Program for Optimizing Diamond Interchanges in Oversaturated Conditions

Abstract: Traditionally, optimization of diamond interchange timings has been done with PASSER III for standard and special diamond phasing sequences. PASSER III is limited because it is designed for undersaturated conditions. It applies vertical stacking of queues and is not capable of modeling queue spillback conditions in its current form. This deficiency is addressed by the arterial signal coordination software (ASCS), whose capabilities in timing diamond interchanges in under-saturated and oversaturated conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Stopped delay was a metric used by the authors to evaluate the performance and select offsets. In other studies, microsimulation (15) was used within hardware-in-theloop (16) or software-in-the-loop (17) configurations to assess total delay (18), cycle length (19), actuation (20), and coordination with adjacent eight-phase intersections (21).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Stopped delay was a metric used by the authors to evaluate the performance and select offsets. In other studies, microsimulation (15) was used within hardware-in-theloop (16) or software-in-the-loop (17) configurations to assess total delay (18), cycle length (19), actuation (20), and coordination with adjacent eight-phase intersections (21).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…One of the most widely used safety metrics of TCT is the Time-To-Collision (TTC) ( Laureshyn et al, 2016 , Mahmud et al, 2019 , Wang and Stamatiadis, 2014 ). Using TTC, different traffic states can be identified in the famous NGSIM database ( Kovvali et al, 2007 ), with the states shown to correspond to different levels of risk ( Zhao et al, 2018 ). The potential risk for human drivers in dangerous car following situations can be assessed ( Liu et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…There are other related literatures (e.g. ), where most reported that GA‐based algorithms perform better at generating timing plans than most other optimization tools, despite its computationally intense nature.…”
Section: Signal Optimizationmentioning
confidence: 99%